Post‐COVID‐19 condition in the German working population: A cross‐sectional study of 200, 000 registered stem cell donors. (18th December 2022) - Bernas, Stefanie N.; Baldauf, Henning; Real, Ruben; Sauter, Jürgen; Markert, Jan; Trost, Sarah; Tausche, Kristin; Behrends, Uta; Schmidt, Alexander H.; Schetelig, Johannes
Abstract: Background: The SARS‐CoV‐2 pandemic has strained health systems worldwide, and infection numbers continue to rise. While previous data have already shown that many patients suffer from symptoms for months after an acute infection, data on risk factors and long‐term outcomes are incomplete, particularly for the working population. Objectives: We aimed to provide information on the prevalence of post‐COVID‐19 conditions in a subset of the German working‐age population (18–61 years old) and to analyze risk factors. Methods: We conducted an online survey with a health questionnaire among registered potential stem cell donors with or without a self‐reported history of polymerase chain reaction (PCR)‐confirmed SARS‐CoV‐2 infection. Logistic regression models were used to examine the risks of severity of acute infection, sex, age, body mass index, diabetes mellitus, and arterial hypertension medication on post‐COVID‐19 symptoms. Results: A total of 199, 377 donors reported evaluable survey questionnaires—12, 609 cases had a history of SARS‐CoV‐2 infection and 186, 768 controls had none. Overall, cases reported physical, cognitive, and psychological complaints more frequently compared to controls. Increased rates of complaints persisted throughout 15 months postinfection, for example, 28.4%/19.3% of cases/controls reported fatigue ( p <0.0001) and 9.5%/3.6% of cases/controls reported loss of concentration ( p <0.0001). No significant differences were observed in the frequency of reported symptoms between 3 and 15 months postinfection. Multivariate analysis revealed a strong influence of the severity of the acute SARS‐CoV‐2 infection episode and age on the risk for post‐COVID‐19 conditions. Conclusion: We report the prevalence of post‐COVID‐19 conditions in mainly unvaccinated individuals with SARS‐CoV‐2 infections between February 2020 and August 2021. The severity of the acute course and age were major risk factors. Vaccinations may reduce the risk of post‐COVID‐19 conditions by reducing the risk of severe infections. Abstract :